2014
DOI: 10.1186/1878-5085-5-3
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of the phosphatase, PP2A is a common event in breast cancer, predicting sensitivity to FTY720

Abstract: BackgroundThe most commonly used biomarkers to predict the response of breast cancer patients to therapy are the oestrogen receptor (ER), progesterone receptor (PgR), and human epidermal growth factor receptor 2 (HER2). Patients positive for these biomarkers are eligible for specific therapies such as endocrine treatment in the event of ER and PgR positivity, and the monoclonal antibody, trastuzumab, in the case of HER2-positive patients. Patients who are negative for these three biomarkers, the so-called trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
3

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 54 publications
3
32
0
3
Order By: Relevance
“…Depending upon the physiological requirements of the cell, proteins transiently shift from a phosphorylated to a dephosphorylated state, with the balance controlled by protein kinases and phosphatases (30,31). PP2A, a serine/threonine protein phosphatase, has been previously suggested to be a tumor suppressor protein in AIs-resistant ER-positive breast cancer cells (17,28,32). In the present study, PP2A tumor suppressor activity was first observed upon treatment with OA, a selective but not specific inhibitor of PP2A, which potently promoted resistance to E 2 deprivation in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Depending upon the physiological requirements of the cell, proteins transiently shift from a phosphorylated to a dephosphorylated state, with the balance controlled by protein kinases and phosphatases (30,31). PP2A, a serine/threonine protein phosphatase, has been previously suggested to be a tumor suppressor protein in AIs-resistant ER-positive breast cancer cells (17,28,32). In the present study, PP2A tumor suppressor activity was first observed upon treatment with OA, a selective but not specific inhibitor of PP2A, which potently promoted resistance to E 2 deprivation in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 57%
“…PP2A is involved in endocrine therapy resistance (28). Therefore, MCF-7 cells cultured without steroids were examined after 1 or 5 days, which activated mTOR.…”
Section: E 2 Deprivation Reduces Pp2a Levels In Mcf-7 Cellsmentioning
confidence: 99%
“…In addition, molecular classification into therapeutic groups shall provide a better understanding of actionable pharmacogenetic biomarkers [17], and potentially targeting new proteins for better treatment [18]. The proper use of biomarkers and the utilization of archival material, with readily available clinical outcome data, provides proper implementation of personalised medicine [19].…”
Section: Discussionmentioning
confidence: 99%
“…9,11,18 Of note, CIP2A is weakly expressed in normal breast tissue as protein and transcript. 7,15 Similar to the study of Tseng et al (2012) 37 and Choi et al, 38 in this study the H-score was used to obtain more information on the distribution of CIP2A scores and intensities.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification/gain of CIP2A as well as overexpression of CIP2A is fairly common across various tumour types. [9][10][11] Various studies have associated higher CIP2A expression with grade, highly proliferative tumours, and stage in distinct tumour types such as prostate, gastric, colon, breast, head and neck squamous cell carcinoma, and ovarian cancer. 7,9,[12][13][14][15][16][17] Our interest in CIP2A stems from its inhibitory activity on protein phosphatase 2A (PP2A), which results in protection of MYC from dephosphorylation thereby stabilising the oncogenic stimulation of MYC on cell proliferation.…”
Section: Introductionmentioning
confidence: 99%